Performance evaluation and damage assessment of buildings subjected to seismic loading - Chandrasekaram S.; Serino G.; Gupta V. (My University, 2025)
The intent of performance-based earthquake engineering is to provide methods for designing, constructing and maintaining buildings, such that they are capable of providing predictable performance when affected by earthquakes. This methodology examines the behavior of a structure at various service levels. Inherently, the performance-based design concept implies the definition of multiple target performance (damage) levels that are expected to be achieved, or at least not exceeded, when the structure is subjected to earthquake ground motion of a specified intensity. Pushover analysis is one of the tools for estimating earthquake demands at various performance levels. This paper focuses on the pushover analysis of multistory structures subjecting them to monotonically increasing lateral forces with an invariant height wise distribution until the preset performance level (target displacement) is reached. It also discusses the collapse mechanism illustrating the sequence of plastic hinge formation before failure with a special mention to the various performance levels namely immediate occupancy (IO), life safety (LS) and collapse prevention (CP) respectively. Conclusions are drawn based on the numerical studies conducted to emphasis the parameters associated with the performance based design of multistory RC framed buildings.